STRATEGI PT. ADIKARYA DISTRIBOGA DALAM MENINGKATKAN VOLUME PENJUALAN - Farida Yanti Br. Simbolon; Paulus A. Pangemanan; Yolanda P.I. Rori (AGRI-SOSIOEKONOMI, 2017)
The purpose of this research was to analyze the alternative strategy to increase the volume of sales in Adikarya Distriboga Ltd Inc. The research was in September until October 2016. The primer data and secondary data were used in this research. Primer data was obtained in interview and questionnaire to four official employees. The analyzing tools of the research were Matrix Internal Factor Evaluation (IFE), Matrix External Factor Evaluation (EFE), Matrix Internal-External (IE) and analyzing SWOT (strengths, weakness, opportunities, threats). The result of this research showed that strategy of Adikarya Distriboga Ltd was in quadrant I. It was aggressive strategy (to expand marketing segment). Strategy of expanding market share can be done by opening new branches, increasing cooperation with the factory in order to always be available stock of wheat to meet demand, improve collaboration with customers, improve service good and friendly to customers and loyal to customers.